THE TRANSLATION OF THE LEXEME “RAIN” IN SAPARDI DJOKO DAMONO’S POETRY ANTHOLOGY ”HUJAN BULAN JUNI” INTO MANDARIN CHINESE: A STUDY OF TRANSLATION STRATEGIES - Rachel Leona Davita Purwanto; Tatang Hariri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study analyzes the Mandarin Chinese translation of the poetry anthology "Hujan Bulan Juni" by Sapardi Djoko Damono, translated by T. F. Chan. The study is motivated by the challenges of translating poetry between two languages with distinct typological characteristics: Indonesian, an agglutinative language, and Mandarin Chinese, an isolating and tonal language. The objectives of this study are to reveal the forms of translation shifts, identify the dominant translation strategies, and analyze the realization of lexical meaning equivalence, particularly in the lexeme "rain". This research adopts a comparative approach by examining fifteen (15) pairs of poems in Indonesian as the source language (SL) and Mandarin Chinese as the target language (TL). The analysis focuses on shifts in textual quantity, structural organization, and semantic meaning. The study uses Newmark's translation theory and Venuti's concepts of domestication and foreignization. The findings indicate that the translator tends to use a domestication strategy. This is evident in how the poems' visual forms are reconstructed to conform to the aesthetic norms of Chinese poetry. There are significant structural shifts created by expansion and reduction, resulting from grammatical differences. Modulation techniques are applied to the lexeme "rain" to achieve emotional and metaphorical equivalence. The translator acts as a bridge, prioritizing acceptability and communicative function for the target readers. The meaning of the source text remains unchanged.